The neonatal Fc receptor is expressed by human retinal pigment epithelial cells and is downregulated by tumour necrosis factor-alpha. Issue 6 (7th January 2011) - van Bilsen, Kiki; van Hagen, P Martin; Bastiaans, Jeroen; van Meurs, Jan C; Missotten, Tom; Kuijpers, Robert W; Hooijkaas, Herbert; Dingjan, Gemma M; Baarsma, G Seerp; Dik, Willem A
Abstract : Background/aims: The neonatal Fc receptor (FcRn) protects immunoglobulin G (IgG) from catabolism, controls its transport between cell layers and extends its serum half-life. In the human, vitreous IgG can be found, but how vitreous IgG is processed or transported is currently unknown. The FcRn is a candidate molecule to regulate these processes. The authors examined FcRn expression and regulation in human retinal pigment epithelium (RPE) cells. Methods: In three primary RPE cell cultures (from three donor eyes) and in the human RPE cell line ARPE-19, FcRn and beta-2-microglobulin (β2M) mRNA levels were determined by real-time quantitative PCR. FcRn protein expression was analysed by western blot studies. Stimulation experiments were performed with recombinant human tumour necrosis factor (TNF)-α and interferon (IFN)-γ. HT-29, THP-1 and HeLa cell lines were used as FcRn positive and negative non-ocular controls, respectively. Results: Expression of FcRn mRNA and protein was demonstrated in all three RPE cultures. After stimulation with TNF-α, FcRn expression is downregulated in RPE cells and upregulated in HT-29 and THP-1 cells. IFN-γ has no effect on FcRn expression in RPE cells. Conclusions: Human RPE cells express FcRn. The proinflammatory cytokine TNF-α downregulates FcRn expression. The authors speculate that the FcRn may play a pivotal role in the immune privilege of the human eye.